3x-4+-2x=-5+5x

Simple and best practice solution for 3x-4+-2x=-5+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-4+-2x=-5+5x equation:


Simplifying
3x + -4 + -2x = -5 + 5x

Reorder the terms:
-4 + 3x + -2x = -5 + 5x

Combine like terms: 3x + -2x = 1x
-4 + 1x = -5 + 5x

Solving
-4 + 1x = -5 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-4 + 1x + -5x = -5 + 5x + -5x

Combine like terms: 1x + -5x = -4x
-4 + -4x = -5 + 5x + -5x

Combine like terms: 5x + -5x = 0
-4 + -4x = -5 + 0
-4 + -4x = -5

Add '4' to each side of the equation.
-4 + 4 + -4x = -5 + 4

Combine like terms: -4 + 4 = 0
0 + -4x = -5 + 4
-4x = -5 + 4

Combine like terms: -5 + 4 = -1
-4x = -1

Divide each side by '-4'.
x = 0.25

Simplifying
x = 0.25

See similar equations:

| 9x=3+7x | | x:17=2 | | 16x+8y+40x= | | y=-0.60*45+141 | | y=-0.60*35+141 | | 8+5x=-20+x | | x^2-12x-1=-3 | | y=-0.60*25+141 | | 6=5(x+2)-7x | | ln(t)-2= | | 1xY-60xX= | | 13Y-12X+14Z=12Y+14Z+48X | | -5x+2y+z= | | 5x+2y-z= | | 15x^2+10x-9=0 | | 2(5)=16-(-6) | | -49=2x+3x+6 | | X+7=14X+7-7 | | 145-342=2 | | 6x+7-7x=3 | | -10x=-4+2x | | 8=2(2c-5)c | | 13z+9=8-3z+2 | | 2x=(1/50) | | 12q=6 | | 6v^2-100=10v | | 3ln(2x+8)=14 | | 10p-7+2-1=3+5 | | 1/11 | | 2/7=x/100 | | 40x-9=71 | | 3t+10=4t+5 |

Equations solver categories